Taxonomic Revision of Hook-Forming Acrosorium (Delesseriaceae, Rhodophyta) from the Northwestern Pacific Based on Morphology and Molecular Data - Jeong Chan Kang (MDPI AG, 2021)
Cosmopolitan Acrosorium species with hook-forming thalli have been merged under the name of Acrosorium ciliolatum (Harvey) Kylin through a long and complicated nomenclatural history. We examined the specimens of ‘A. ciliolatum’ and related taxa from the northwestern (NW) Pacific, the UK, southern Spain, Australia, New Zealand, and Chile, using morphological and molecular analyses. We confirmed that these specimens are separated into four clades based on rbcL phylogeny, and the absence or presence of terminal hook-like structures represent intraspecific variation. Our results indicated that Acrosorium flabellatum Yamada, Cryptopleura hayamensis Yamada, Cryptopleura membranacea Yamada and the entities known as ‘A. ciliolatum’ in the NW Pacific are conspecific; the name A. flabellatum is the oldest and has priority. This taxon exhibits extreme variations in external blade morphology. We also confirmed that the position of the tetrasporangial sori is a valuable diagnostic characteristic for distinguishing A. flabellatum in the NW Pacific. We also discussed the need for further study of European and southern hemisphere specimens from type localities, as well as the ambiguous position of California specimens.